The spatial pattern analysis of settlements area in Batusangkar City Tanah Datar Regency - Rery Novio; Sri Mariya; Bayu Wijayanto (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2020)
The spatial distribution of populations and settlements is in line with connectivity and accessibility within a city area. Delineation of Batusangkar City exists in 3 sub-districts and 6 Nagari, causing settlement concentration in certain areas will form a certain distribution pattern and different settlement, the occurrence of diversity patterns distribution as a form of uneven population distribution. So that information is needed regarding changes in land use and patterns of settlement distribution concerning land use in urban planning. This study aims to discover the changes in area and distribution patterns of settlements. This research method is quantitative descriptive using secondary data and then analyzed using the nearest neighbor analysis. The results of the study showed the change in the distribution of settlements to areas close to public facilities such as offices, schools, and universities. Batusangkar City area has a Pureisolated type pattern, while based on the Alvin L. Bertrand category it has a Line Village Community pattern, then based on the calculation of the nearest neighbor analysis it is categorized as Clustered